PENGARUH PEMBERIAN COMPLETE FEED DENGAN KEDELAI TERPROTEKSI TERHADAP ASAM LEMAK TIDAK JENUH PADA SUSU SAPI PERANAKAN FRIESIAN HOLSTEIN - , VITA KRISNADEWI S. PT., Ir. Subur Priyono Sasmito Budhi, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of the study was to find out the effect of complete feed with protected soybean on the production and quality of milk from Friesian Holstein crossbred dairy cows. It used six Friesian Holstein crossbred dairy cows with initial body weight of 334+36.5 kg were devided into two groups, and each was given control feed (P1) and complete feed with protected soybean (P2) using crossed over design at the third and fifth months of lactation period. Variables measured were dry matter intake (DMI), digestibility, daily milk production, and milk quality. The DMI showed that there were a significant differences (P<0.05), i.e. in P1 of 11.12 kg lower than that of P2 of 11.30 kg. The digestibility showed that there were a very significant differences (P<0.01), i.e. in P1 of 76.14% higher than that P2 of 70.05%. The milk production, fat content, protein, and total solid showed that there were no significant differences between P1 and P2. Average production of milk at P1 was 7.649 liter/day, while P2 was 7.248 liter/day. Milk fat, protein and total solid in P1 were 3.29%, 2.61% and 11.12%, respectively, while P2 were 3.24%, 2.65%, and 11.15%, respectively. The specific mass of milk showed that there were a significant differences (P<0.05), i.e. in P1 of 1.025 lower than in P2 of 1.026. The unsaturated fatty acids of linoleic acid and cervonic acid in P1 were 0.16 (mg/100ml) and 0.07 (mg/100ml), respectively, higher than that P2 of 0.14 (mg/100ml) and 0.05 (mg/100 ml), respectively (P<0.05). It can be concluded that complete feed with protected soybean can be used as an alternative feed for dairy cows.